The influence of promotion, product image, and product quality on repurchasing decisions of Chatime products (Case study on Chatime consumers in South Tangerang City) - Kayla Zoraya Hanum; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Privietlab, 2022)
This study aims to determine the effect of Promotion, Product Quality, and Brand Image on Repurchasing Decisions on Chatime Products in South Tangerang City. This study used quantitative research with a sample of 100 respondents, using the Lemeshow formula. Data collection techniques using questionnaires in the form of Gform. The analytical method used is multiple linear regression using the SPSS application as a data processing tool. The results of this study can be seen from the results of multiple linear regression tests with the results of promotion, product quality, and brand image having a positive effect on repurchasing decisions for Chatime products in South Tangerang. The results of the t test show that promotion and brand image have no significant effect on repurchasing decisions